Investigating the impact of effective risk management on the performance of Malaysian publicly listed companies - Saad, Masrina Md; Ismail, Rina Fadhilah; Zam, Zuraidah Mohd; Hasnan, Suhaily (Edelweiss Applied Science and Technology, 2024)
Risk management functions as a communication tool, conveying a company’s proactive strategies to investors for addressing potential threats. Emphasizing the management of risk and uncertainty proves beneficial for maximizing shareholder value by achieving robust financial performance. Financial performance, employed to discern superior and relevant information, plays a pivotal role in assessing the current financial situation and forecasting future performance. This research explores the intricate relationship between effective risk management and the performance of publicly listed companies in Malaysia. As a quantitative investigation, it involves a robust dataset of 1,216 year-observations spanning four years, from 2018 to 2021, with a specific focus on publicly listed entities. Tobin’s Q assesses firm performance, while the effectiveness of risk management is scrutinized by evaluating key risk objectives, including strategy risk, operational risk, reporting risk, and compliance risk. Control variables, such as company size and leverage, are integrated into the research framework. The findings indicate that all key risks, representing effective risk management, significantly influence the firm performance of Malaysian publicly listed companies. This study not only contributes empirical substance to the ongoing discourse on risk management but also offers valuable insights into how the effectiveness of risk management practices impacts the performance of publicly listed companies within the Malaysian context. The research is a significant source of knowledge for investors, executives, and scholars who want to understand the complex relationship between risk management effectiveness and corporate success in the Malaysian public-listed sector.